2003
DOI: 10.1038/sj.leu.2402788
|View full text |Cite
|
Sign up to set email alerts
|

Aplidine, a new anticancer agent of marine origin, inhibits vascular endothelial growth factor (VEGF) secretion and blocks VEGF-VEGFR-1 (flt-1) autocrine loop in human leukemia cells MOLT-4

Abstract: The mechanism by which aplidine, a marine natural product in early clinical development as an anticancer agent, induces cell growth inhibition and apoptosis has been investigated in the human leukemia cell line MOLT-4. This cell line is characterized not only by the ability to secrete VEGF, but also for the presence on its surface of the VEGF receptor-1 (VEGFR-1). Previous studies from our laboratory concerned with evaluating early changes in gene expression induced by aplidine in MOLT-4 cells have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 29 publications
(35 reference statements)
2
85
0
4
Order By: Relevance
“…The present study also shows that Aplidin is a strong inducer of apoptosis, a finding in keeping with previous data obtained on another human leukaemia Molt-4 cell line (Erba et al, 2002;Broggini et al, 2003). In all the cell lines investigated, the Aplidininduced cell death was clearly related to the induction of apoptosis, even if in Reh cells the apoptosis was found only when the cells were exposed to high concentrations of Aplidin.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study also shows that Aplidin is a strong inducer of apoptosis, a finding in keeping with previous data obtained on another human leukaemia Molt-4 cell line (Erba et al, 2002;Broggini et al, 2003). In all the cell lines investigated, the Aplidininduced cell death was clearly related to the induction of apoptosis, even if in Reh cells the apoptosis was found only when the cells were exposed to high concentrations of Aplidin.…”
Section: Discussionsupporting
confidence: 92%
“…We have recently reported that in Molt-4 cells Aplidin causes an inhibition of VEGF secretion and a downregulation of flt-1 (Broggini et al, 2003). The apoptosis induced by Aplidin in Molt-4 cell could be observed also by exposing the leukaemic cells to anti-VEGF antisense oligonucleotide (Gerber et al, 1998;Nor et al, 1999;Broggini et al, 2001Broggini et al, , 2003.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations